2008
DOI: 10.1088/0953-8984/20/50/505215
|View full text |Cite
|
Sign up to set email alerts
|

Structure and phase transition of Na0.5La0.5TiO3

Abstract: A temperature dependent neutron powder diffraction study was carried out on Na 0.5 La 0.5 TiO 3 (NLT) from 298 K up to 1373 K. Rietveld analysis using high resolution x-ray and neutron powder diffraction data confirmed the rhombohedral structure (space group R 3c) of this compound. The rhombohedral phase transforms to cubic (Pm 3m) above 873 K. The temperature variation of the tilt angle, a continuous change of the specific volume across the transition, and the strain analysis suggest a second order nature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Structural characterisation of La0.5Na0.5TiO3 (LNTO) with synchrotron powder X-ray and neutron diffraction gave good agreement with the reported rhombohedral structure (Fig. S1, Table S2, ESI †), 31 most importantly highlighting that La 3+ and Na + are fully disordered on the A site. Despite this, the anisotropic displacement parameters do not indicate a strong local deviation away from the average structure with a root mean square displacement of 0.078(9) Å for the A site at 300 K, showing that Please do not adjust margins Please do not adjust margins LNTO is a crystalline solid with disordered A site cation distribution.…”
supporting
confidence: 72%
“…Structural characterisation of La0.5Na0.5TiO3 (LNTO) with synchrotron powder X-ray and neutron diffraction gave good agreement with the reported rhombohedral structure (Fig. S1, Table S2, ESI †), 31 most importantly highlighting that La 3+ and Na + are fully disordered on the A site. Despite this, the anisotropic displacement parameters do not indicate a strong local deviation away from the average structure with a root mean square displacement of 0.078(9) Å for the A site at 300 K, showing that Please do not adjust margins Please do not adjust margins LNTO is a crystalline solid with disordered A site cation distribution.…”
supporting
confidence: 72%
“…Using a combination of synchrotron and neutron powder diffraction data, Garg et al showed that R3¯c was a better description of the structure of Na 0.5 La 0.5 TiO 3 than I 4 /mcm . The octahedral tilting about the hexagonal [001] was quantified at about 8°.…”
Section: Introductionmentioning
confidence: 90%
“…Others later proposed an orthorhombic structure in space group Pnma . Most recently, several groups have used synchrotron‐ and neutron‐diffraction data to establish either tetragonal ( I 4 /mcm ) or trigonal (R3¯c) structural models, with a phase transition to an orthorhombic form in the region 0 < x < 0.05. Knapp & Woodward suggested that the A‐site ordering observed in the analogous perovskite (Na 0.5 La 0.5 )(Mg 0.5 W 0.5 )O 3 would imply that Na 0.5 La 0.5 TiO 3 should also have A‐site cation ordering; however, they observed no such long‐range ordering.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, Δ r A can be used explicitly as a measure of A‐site ordering. Interestingly, while no evidence of long‐range A‐site ordering has been observed in the NLT system via x‐ray or neutron diffraction, this model clearly shows the pattern of errors leading to the conclusion of order. In fact, electron diffraction shows that the structure consists of nanodomains of order (short‐range order); thus, even short‐range order can be quantified with this model.…”
Section: Introductionmentioning
confidence: 69%